Utilization of Wordwall in Iqra Learning: Technological Innovation to Improve Religious Literacy of Early Childhood in Tadika Mysarah Alfikh Orchard - Veronica, Anggie; Harfiani, Rizka (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the use of wordwall media in Iqra learning at Tadika Mysarah Alfikh Orchard and the challenges faced in its implementation. The research method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the use of wordwall media can increase student learning motivation, student participation, and accelerate their understanding of the hijaiyah letters. In addition, interviews with teachers and students showed that this media can make learning more interesting. However, there are several challenges in implementing wordwalls, such as limited digital devices, teacher adaptation to digital technology, and dependence on internet connections. To overcome these obstacles, several solutions are suggested, namely by procuring devices in schools, providing technology training for teachers, and developing alternative offline learning. Overall, this study concludes that wordwall media is an effective learning media in improving the quality of Iqra learning for early childhood, with the note that technical and pedagogical challenges must be managed properly.